A Review on Vehicular Ad Hoc Network (VANET) Security challenges and Solutions - Lawal B. IDRIS (FUDMA Journal of Engineering and Technology, 2025)
Vehicular Ad Hoc Networks (VANETs), enable communication between moving vehicles called nodes and roadside infrastructures. These communications are meant to increase driver assistance, efficiency, and traffic safety. From a security and privacy perspective, the vehicles in these systems are open to Sybil, DoS or DDoS attacks. The main areas of concern in VANETs are security and privacy of users. This research was aimed at reviewing security issues in Vehicular Ad Hoc Networks (VANETs), taking a closer look at how these networks are struggling with real-world threats. It examined a range of incidents recently reported and various ways attackers get into these networks and identifying vulnerabilities like insider attacks, denial-of-service (DoS), and the challenges of current cryptographic solutions. There is a clear indication that the security frameworks currently rely on are failing; insider attacks, DoS attacks, and weak encryption solutions seem to manifest themselves. However, these networks are key for vehicle communication as well as control and can seriously affect public safety. It is obvious that stronger solutions are needed to keep data and user privacy in a safe manner. Therefore, this study not only identified and explained the vulnerabilities in VANET but also offers some basic recommendations for building strong security frameworks in the networks.
Keywords: Challenges, review, security, solutions, VANETs.